2017
DOI: 10.1021/acs.iecr.7b00760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cubic Plus Association Equation of State Predictive Capacities: A Study on the Transferability of the Hydroxyl Group Associative Parameters

Abstract: To create a predictive method for an associative equation of state, the parameters of a specific associative group should be transferrable among molecules. The hydroxyl group, one of the most common associative groups, is a good starting point for this development. On the basis of a previous study where a modified version of the Cubic Plus Association (CPA) EoS was shown to present accurate results for alkanols with almost constant association parameters, this work addresses branched, secondary alcohols, 1,ω-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…The overall good results are due to the accurate values of the ideal heat capacity (Cp id ), which is most often the main contribution. 18,35,46 In order to illustrate the above, we calculated the percentage of Cp id /Cp for water with the results from the NIST chemistry webbook 58 at saturated condition and different pressures. The results are shown in Figure 1.…”
Section: Other Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall good results are due to the accurate values of the ideal heat capacity (Cp id ), which is most often the main contribution. 18,35,46 In order to illustrate the above, we calculated the percentage of Cp id /Cp for water with the results from the NIST chemistry webbook 58 at saturated condition and different pressures. The results are shown in Figure 1.…”
Section: Other Resultsmentioning
confidence: 99%
“…Palma et al proposed a modified CPA EoS to calculate the C v , C p , C v res , and C p res of alcohols and water at saturation. In their works, the original α function (one parameter) was replaced by a 5-parameter function, and two different kinds of ( T -independent and T -dependent) volume shifts were added to the EoS.…”
Section: Discussion Of the Performance Of Different Equations Of Statementioning
confidence: 99%
See 2 more Smart Citations
“…Past studies for CPA have shown that the same association energy is transferrable between alcohols and glycols. 56,57 On the other hand, past studies for PC-SAFT have shown that these parameters are not transferrable and that the association energy of glycols (2080 K) is much lower than that of alcohols (2811 K). 58,59 No root cause was identified for why the optimum PC-SAFT ethylene glycol association energy falls far below all other alcohol parameters (PC-SAFT and CPA) and glycol parameters (CPA).…”
Section: Association Parameter Estimation Workflowmentioning
confidence: 98%